Pengaruh Kemanfaatan, Promosi, dan Kualitas Pelayanan terhadap Minat Penggunaan E-Money Gopay di Jawa Tengah - Islamiah, Makrufah Hidayah; Purwanto, Ivani; Gunawardana, Khayana Tirtha; Arrosyad, Enggar (Universitas Islam Negeri Sunan Kudus, 2020)
Electronic money is growing rapidly now, people are required to follow quickly and adapt so they are not less competitive. Electronic money products issued by non-banking institutions, one of which is Gopay. This research was conducted with the aim of knowing the influence of people in Central Java regarding electronic money on the interest in using e-money Gopay in Central Java. The research method is quantitative research with a positivism research paradigm approach using a questionnaire method with a total sample of 100 respondents. The results showed that simultaneously the benefits, promotion, and service quality variables had a positive and significant effect. Partially the benefits and promotion variables have a positive and significant effect on interest, but the variable service quality does not have a significant effect on interest.Keywords: usefulness, promotion, service quality, interest